Immunohistochemistry for immunoglobulin G4 in the diagnosis of pemphigus - Mitra Heidarpour; Parvin Rajabi; Elnaz Babaei Pour; Emad Fayyazi (Wolters Kluwer Medknow Publications, 2019)
Introduction: Pemphigus comprises of a group of autoimmune bullous disorders with intraepithelial lesions involving the skin and mucous membranes. Pemphigus is characterized histologically by an intraepidermal blister and immunopathologically by the finding of in vivo bound immunoglobulin G (IgG) antibodies against desmosomal adhesion proteins on the surface of keratinocytes. Indirect immunofluorescence for IgG is considered as a gold standard method for diagnosis of this group of bullous disorders on the condition that fresh frozen tissue is accessible. Aim: We designed a new diagnostic method by immunohistochemistry (IHC) for IgG4 on paraffin sections instead of fresh frozen tissue and evaluated sensitivity, specificity, and positive and negative predictive values of this method. Materials and Methods: We searched our pathologic archive of pemphigus of 35 patients, including 29 cases of pemphigus vulgaris (PV) and 6 patients with pemphigus foliaceus (PF). In all cases, the diagnosis was confirmed by indirect immunofluorescence studies. Thirty-five specimens served as controls, including 31 specimens of safe margins of basal cell carcinoma and 4 specimens of normal skin. Sections with condensed and continuous immunoreactivity localized to the intercellular junctions of keratinocytes were considered as positive. Results: Sensitivity of IgG4 was estimated to be 72.4% in PV group and 83.3% in PF group. The overall sensitivity and specificity of IgG4 IHC for diagnosis of pemphigus were 74.2% and 82.8%, respectively, in PV and PF groups. Furthermore, positive predictive value and negative predictive value were 81.2% and 76.3%, respectively. Conclusion: Immunohistochemical labeling for IgG4 on paraffin-embedded tissue provides a sensitive and specific test for diagnosing pemphigus in a situation when fresh frozen tissue is unavailable.